An Analytical Approach to Machine Layout Design at a High-Pressure Die Casting Manufacturer - EMİR, OĞUZ; AKTİN, AYŞE TÜLİN (Springer-Verlag Singapore Pte Ltd., 2022)
Sahin Metal was founded in 1975 on a 7500 m(2) area in.Istanbul to supply high-pressure aluminum casting parts to a variety of industries, especially automotive manufacturers. 64 different products are produced with various routings through 14 workstations in the plant. Being a Tier 2 company, these products are then sent to Tier 1 firms and finally reach the leading vehicle manufacturers. Nowadays, increasing competition, changing customer demands, and quality targets bring the necessity of restructuring internal processes. In this regard, Sahin Metal plans to rearrange the existing machine layout to minimize the distance traveled between departments by taking into account the material flow. This study aims to determine an efficient machine layout design by implementing analytical approaches. The study is started by visiting the production facility and meeting with the company's engineers to determine the project roadmap. Following that, the data collection process is initiated, and ABC analysis is performed to define product classes. After this identification, two approaches are utilized simultaneously. The Hollier method is employed to find a logical machine arrangement. In addition, a mathematical model based on the Quadratic Assignment Problem (QAP) is developed to obtain the optimum machine layout. The developed integer nonlinear model is solved by CONOPT using GAMS software under various scenarios. Finally, these results are compared with the existing system, and a convenient layout design is proposed to the company.
21st International Symposium on Production Research (ISPR) - Digitizing Production System
▪ Book Series: Lecture Notes in Mechanical Engineering.
Keywords: Facilities Design and Planning; Machine Layout Design; Nonlinear Programming